Three‐years clinical outcome of immediate provisionalization of single Osseospeed™ implants in extraction sockets and healed ridges. Issue 2 (2nd April 2012) - De Bruyn, Hugo; Raes, Filiep; Cooper, Lyndon F.; Reside, Glenn; Garriga, Joan S.; Tarrida, Luís G.; Wiltfang, Jörg; Kern, Matthias
Abstract Aim The purpose of this prospective multicenter clinical study was to compare 3 years implant survival, bone and soft tissue changes following immediate loading using single Osseospeed™ implants (Astra Tech AB, Mölndal, Sweden) installed in healed ridges or extraction sockets. Material and methods Implants were provisionally restored the day of surgery using cemented acrylic crowns out of full occlusion. The provisional crowns were replaced after 12 weeks by full‐ceramic crowns. Implant survival, bone levels, soft tissue levels and peri‐implant health were monitored up to 3 years. Results 55 patients (22 men, 33 women; mean age 45) had the implant installed in extraction sockets and 58 patients (25 men, 33 women; mean age 42) received conventional implant treatment in healed ridges. Three implants failed in the extraction group and one implant failed in the healed group, all failures occurred before the final crown placement. No further losses occurred during 3 years, giving a statistically comparable survival rate of 94.6% and 98.3%, respectively. The total bone loss after 3 years, compared to implant placement was 0.4 mm (SD 1.5) in healed sites, whilst the immediate sites showed a bone gain of 1.6 mm (SD 2.4) due to bone fill in the alveolus. Papillae retracted with 0.3 and 0.0 mm in the period of provisionalization, but grew back after final crown was placed with 0.3 and 0.5 mm in extraction and healed sites respectively after 3 years. Plaque and inflammation scores were very low throughout the study time, irrespective of treatment modality. Conclusions Immediate implants restored at the day of surgery show comparable risk for implant failure, bone loss and midfacial soft tissue recession compared to conventionally installed implants. The 3‐years results suggest both hard and soft tissue stability.